Perlindungan Hukum Preventif Terhadap Ekspresi Budaya Tradisional di Daerah Istimewa Yogyakarta Berdasarkan Undang-Undang Nomor 28 Tahun 2014 Tentang Hak Cipta - Asri, Dyah Permata Budi (Fakultas Hukum Universitas Islam Indonesia, 2018)
This research aims to get an overview of the legal protection of traditional cultural expressions in the Yogyakarta that will maintain several cultures from ownership claims by other parties or other nations. For this reason, efforts are needed so that the culture can be preserved from destruction and loss of culture due to claims of ownership by other parties. This research is a normative juridical research that takes data in the field as primary material. The result of this study is to protect against traditional cultural expressions which are communal, which is very different from the general intellectual property regime such as song copyrights, marks, patents which are very individualistic. The regulation regarding its proper protection component is carried out by using preventive protection as practiced by the Department of Culture of the Yogyakarta Province and the Culture and Tourism Office of Sleman Regency, namely by conducting cultural inventory and documentation, as mandated in Law Number 28 of 2014 concerning Copyright especially Article 38. Recording of non-material cultural heritage is considered important because some elements of cultural heritage do not begin to be threatened with extinction or potentially claimed ownership by other countries. Until 2016, 444 intangible cultural works were registered as Indonesian Intangible Cultural Heritage managed by the Directorate General of Culture, Ministry of Education and Culture. While the Yogyakarta Department of Culture has attempted to carry out an inventory of several cultures in Yogyakarta. There are 22 (twenty-two) cultural works recorded in Yogyakarta that have been designated as intangible cultural heritage of Indonesia.